Hypoxia induces cell damage via oxidative stress in retinal epithelial cells. (March 2014) - Cervellati, F.; Cervellati, C.; Romani, A.; Cremonini, E.; Sticozzi, C.; Belmonte, G.; Pessina, F.; Valacchi, G.
Abstract Retinal diseases (RD), including diabetic retinopathy, are among the most important eye diseases in industrialized countries. RD is characterized by abnormal angiogenesis associated with an increase in cell proliferation and apoptosis. Hypoxia could be one of the triggers of the pathogenic mechanism of this disease. A key regulatory component of the cell's hypoxia response system is hypoxia-inducible factor 1 alpha (HIF-1α). It has been demonstrated that the induction of HIF-1α expression can be also achieved in vitro by exposure with cobalt chloride (CoCl2), leading to an intracellular hypoxia-like state. In this study we have investigated the effects of CoCl2 on human retinal epithelium cells (hRPE), which are an integral part of the blood–retinal barrier, with the aim to determine the possible role of oxidative stress in chemical hypoxia-induced damage in retinal epithelial cells. Our data showed that CoCl2 treatment is able to induce HIF-1α expression, that parallels with the formation of reactive oxygen species (ROS) and the increase of lipid 8-isoprostanes and 4-hydroxynonenal (4-HNE) protein adducts levels. In addition we observed the activation of the redox-sensitive transcription factor nuclear factor-kappaB (NFkB) by CoCl2 which can explain the increased levels of vascular endothelial growth factor (VEGF). The increased number of dead cells seems to be related to an apoptotic process. Taken together these evidences suggest that oxidative stress induced by hypoxia might be involved in RD development through the stimulation of two key-events of RD such as neo-angiogenesis and apoptosis.